Synthesis of polysubstituted 1, 2-dihydroquinolines and indoles via cascade reactions of arylamines and propargylic alcohols catalyzed by FeCl3·6H2O. Issue 8 (28th January 2016) - Shao, Min; Wu, Yunjun; Feng, Zhijun; Gu, Xiaoxia; Wang, Shaoyin
Abstract : Syntheses of 1, 2-dihydroquinolines from arylamines and propargylic alcohols via cascade Friedel–Crafts-type reaction and 6- endo-trig hydroamination catalyzed by FeCl3 ·6H2 O are described. Abstract : An efficient, environmentally friendly and high-yielding route from inexpensive starting materials to 1, 2-dihydroquinolines has been developed. This procedure proceeded via a cascade Friedel–Crafts-type reaction and 6- endo-trig hydroamination under the catalysis of FeCl3 ·6H2 O, involving the formation of two new σ (C–C and C–N) bonds in a single operation for the construction of a 1, 2-dihydroquinoline skeleton in good to excellent yields.